Corporate financial distress, market reaction and turnaround strategies: a Malaysian scenario - Ismail, Norashikin; Wan Abdullah, Wan Razazila; Mohamed Sadique, Raziah Bi (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2004)
This study aims to contribute to the debate on financial distress by examining the market reaction to the announcement of Practice Note 4 (PN4) status for financially distressed companies in Malaysia. The main objective is to examine the share return performance of these companies upon the announcement of PN4 status. A sample of PN4 companies from February 2001 to December 2002 was selected for this study. The annual reports were analyzed in terms of financial performance and turnaround strategies for the period 1999 to 2003. The results show that financially distressed companies experienced significantly poor performance, evidenced by negative average abnormal returns and cumulative abnormal returns in both the short-run and long-run periods following the announcement. There is also significant evidence that recovery and non-recovery firms adopt a similar set of turnaround strategies. However, recovery firms more frequently adopt capital expenditures, equity issues, and asset sales, which can be classified as forward-looking, expansionary, and externally focused strategies. Conversely, non-recovery firms are more internally focused on operational and financial restructuring strategies to overcome the distress situation.